2012
DOI: 10.1093/eurpub/cks029
|View full text |Cite
|
Sign up to set email alerts
|

Gender distribution of suicide attempts among immigrant groups in European countries--an international perspective

Abstract: The higher suicide attempt rates in non-European immigrant females compared with males may be indicative of difficulties in the acculturation processes in Europe. Further understanding of factors underlying suicidal behaviour in immigrant and minority groups is necessary for planning effective prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…A similar trend was found in one of the studies mentioned above, which involved 10 European countries: Turkey, Swizerland, Belgium, Finland, Israel, the Netherlands, Italy, Sweden, Estonia and Germany. In this survey, the highest rates of suicide atempts among migrants generally corresponded to higher rates of suicide in the country of origin, and there was an overlap between the rates of suicide atempts of the same ethnic group in diferent host countries [3]. Similarly, a meta-analysis of 33 studies about the suicide rates in migrants from almost 50 nationalities, in 7 host countries (Australia, Austria, Canada, England, the Netherlands, Sweden and the USA), supported the strong correlation between migrants' suicide rates and those of their countries of origin [12].…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…A similar trend was found in one of the studies mentioned above, which involved 10 European countries: Turkey, Swizerland, Belgium, Finland, Israel, the Netherlands, Italy, Sweden, Estonia and Germany. In this survey, the highest rates of suicide atempts among migrants generally corresponded to higher rates of suicide in the country of origin, and there was an overlap between the rates of suicide atempts of the same ethnic group in diferent host countries [3]. Similarly, a meta-analysis of 33 studies about the suicide rates in migrants from almost 50 nationalities, in 7 host countries (Australia, Austria, Canada, England, the Netherlands, Sweden and the USA), supported the strong correlation between migrants' suicide rates and those of their countries of origin [12].…”
mentioning
confidence: 72%
“…The continuity highlighted by the correlation with suicidality in the migrants' countries of origin may be understood from either a cultural or a genetic perspective. However, the results in this ield are mixed, and while a recent review concluded that, overall, most migrant groups do not have an increased suicide risk relative to the localborn population, with some even experiencing substantially lower risks [15], another one reported higher rates of suicidal behaviors among migrants compared to host populations, which is likely due to diiculties in the acculturation and integration process [3].…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Young women demonstrate high levels of non-fatal suicidal behavior and suicidal ideation compared to males (Bursztein Lipsicas et al, 2012). Nevertheless, there is a paucity of research investigating the…”
Section: Introductionmentioning
confidence: 99%